2018
DOI: 10.1002/cpdd.426
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Tedizolid Phosphate in Elderly Subjects

Abstract: Tedizolid phosphate is approved for the treatment of acute bacterial skin and skin structure infections in adults. We evaluated the pharmacokinetics of tedizolid in elderly subjects to guide dosing recommendations. In an open-label phase 1 study (ClinicalTrials.gov identifier NCT01496677), 14 elderly (≥65 years) and 14 younger control (18-45 years) subjects each received a single oral dose of tedizolid phosphate 200 mg. Blood samples were collected before dose and more than 72 hours after dose. The pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Tedizolid is still not a FDA/EMA-approved antibiotic for the treatment of LRTIs, but it does bring hope to patients suffering liver and kidney organ failure, especially for LRTIs associated with linezolid-resistant Gram-positive pathogens. Although the phase 3 trial (NCT02019420) of tedizolid for HAP has not yet yielded results, tedizolid brings hope to old patients suffering renal or hepatic failure, especially with linezolid-resistant Gram-positive pathogens pneumonia (Flanagan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tedizolid is still not a FDA/EMA-approved antibiotic for the treatment of LRTIs, but it does bring hope to patients suffering liver and kidney organ failure, especially for LRTIs associated with linezolid-resistant Gram-positive pathogens. Although the phase 3 trial (NCT02019420) of tedizolid for HAP has not yet yielded results, tedizolid brings hope to old patients suffering renal or hepatic failure, especially with linezolid-resistant Gram-positive pathogens pneumonia (Flanagan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has a good penetration into skin and soft tissue [ 45 ], a very high oral bioavailability allowing equivalent dosing when switching from IV to PO therapy [ 9 , 12 , 13 ], and convenient once-daily dosing [ 8 , 9 , 12 , 13 ]. In addition, unlike some antibiotics, such as vancomycin, daptomycin or ceftaroline, tedizolid phosphate does not require dose adjustment in special populations, including the elderly, the obese and morbidly obese, and patients with renal or hepatic impairment [ 14 , 46 49 ]. In trials, tedizolid phosphate IV/PO once daily for 6 days demonstrated comparable efficacy to linezolid IV/PO twice daily for 10 days in patients with cellulitis, major cutaneous abscess and wound infection, and similar clinical cure rates were observed in subgroups of patients, including those with higher BMI or moderate/severe renal impairment and the elderly [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no disparity in PK profiles was noted in morbidly obese patients compared to the nonobese subjects [23]. There were no significant Table 1 Pharmacokinetic parameters of tedizolid at a therapeutic dosage (200 mg/day) AUC 0-∞ AUC from zero to infinity, AUC 0-24 AUC from 0 to 24 hours, C max maximum concentration, IV intravenous, SD standard deviation from the mean, V d volume of distribution a AUC = area under the concentration-time curve Data from [4,5,15,18,20,21,25,28]…”
Section: Obese Populationmentioning
confidence: 99%
“… AUC 0–∞ AUC from zero to infinity, AUC 0–24 AUC from 0 to 24 hours, C max maximum concentration, IV intravenous, SD standard deviation from the mean, V d volume of distribution a AUC = area under the concentration–time curve Data from [ 4 , 5 , 15 , 18 , 20 , 21 , 25 , 28 ] …”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation